2017
DOI: 10.1016/j.ophtha.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Teleophthalmology in the United States

Abstract: Telemedicine services facilitate the evaluation, diagnosis, and management of the remote patient. Telemedicine has rapidly flourished in the United States and has improved access to care, outcomes, and patient satisfaction. However, the use of telemedicine in ophthalmology is currently in its infancy and has yet to gain wide acceptance. Current models of telemedicine in ophthalmology are largely performed via “store and forward” methods, but remote monitoring and interactive modalities exist. Although studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
193
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(213 citation statements)
references
References 36 publications
1
193
1
4
Order By: Relevance
“…Newer technology continues to contribute to teleophthalmology efforts, but barriers remain to widespread adoption . However, the Scottish Eyecare Integration project was able to utilize teleophthalmology to reduce wait times and make final diagnosis in 20% of cases without direct consultation .…”
Section: Newer Non‐mydriatic and Handheld Camerasmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer technology continues to contribute to teleophthalmology efforts, but barriers remain to widespread adoption . However, the Scottish Eyecare Integration project was able to utilize teleophthalmology to reduce wait times and make final diagnosis in 20% of cases without direct consultation .…”
Section: Newer Non‐mydriatic and Handheld Camerasmentioning
confidence: 99%
“…47 Newer technology continues to contribute to teleophthalmology efforts, but barriers remain to widespread adoption. 48,49 However, the Scottish Eyecare Integration project was able to utilize teleophthalmology to reduce wait times and make final diagnosis in 20% of cases without direct consultation. 50 In a test of teleophthalmology involving clinical data as well as imaging, virtual review was only found to differ from face-to-face consultation in 3.4% of 204 cases.…”
Section: Newer Non-mydriatic and Handheld Camerasmentioning
confidence: 99%
“…A recent review of the current state of teleophthalmology in the United States noted that teleophthalmology may allow for earlier detection and more reliable monitoring of ocular conditions and has the potential to improve access to care and adherence to evidence-based protocols [11]. Additionally, teleophthalmology has the ability to increase access to subspecialty care, especially for people living in remote locations.…”
Section: Discussionmentioning
confidence: 99%
“…The application of telemedicine expands throughout medicine; accordingly, in glaucoma care, most uses are in disease screening with optic nerve photographs transmitted to glaucoma specialists (93). The ease of acquiring multiple images opens new opportunities for detection of disease progression.…”
Section: Artificial Intelligence and Telemedicinementioning
confidence: 99%